Type of screen time and academic achievement in children from Australia and New Zealand: interactions with socioeconomic status. Issue 4 (2nd October 2021) - Skvarc, David R.; Penny, Anne; Harries, Travis; Wilson, Christopher; Joshua, Nicki; Byrne, Linda K.
ABSTRACT: Increasing screen time in childhood has raised concerns about potential effects on academic achievement, with speculation that this is due in part to an overall decrease in sleep. However, research does not often distinguish between different types of screen time, such as that dedicated to home or other educational pursuits. Further, family factors such as socioeconomic status are known to predict academic performance but are rarely examined in concert. The current study aimed to examine the association between screen time and academic achievement and to extend the current research by exploring whether the association was moderated by the type of screen time and family socioeconomic status. Participants were 651 children from Australia and New Zealand ( Mage   = 10.09, SD  = 3.64). Participants completed an academic achievement test, and parents reported screen time activities. Homework, but not sleep, was associated with better academic achievement. Educational television viewing (TV), but not entertainment TV, was associated with lower academic achievement. Socioeconomic status moderated the association between educational TV and academic achievement ( B = −.29, p = .007). The results suggest that while screen time type does appear to be implicated in academic achievement, the mechanism appears to be specific to higher socioeconomic status families.